2012
DOI: 10.1016/j.jqsrt.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar extinction and interstellar polarization: Old and new models

Abstract: The review contains an analysis of the observed and model curves of the interstellar extinction and polarization. The observations mainly give information on dust in diffuse and translucent interstellar clouds. The features of various dust grain models including spherical/non-spherical, homogeneous/inhomogeneous particles are discussed. A special attention is devoted to the analysis of the grain size distributions, alignment mechanisms and magnetic field structure in interstellar clouds. It is concluded that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 145 publications
2
46
1
Order By: Relevance
“…(2) is not satisfied and the ratio of the total-to-selective extinction R V is only one of the characteristics of the dusty medium and it varies in space as well as with wavelength (Voshchinnikov 2012). This has forced scientists to develop a new branch of science, the physics of cosmic dust.…”
Section: Changes In the Concept Of Interstellar Extinctionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2) is not satisfied and the ratio of the total-to-selective extinction R V is only one of the characteristics of the dusty medium and it varies in space as well as with wavelength (Voshchinnikov 2012). This has forced scientists to develop a new branch of science, the physics of cosmic dust.…”
Section: Changes In the Concept Of Interstellar Extinctionmentioning
confidence: 99%
“…This has forced scientists to develop a new branch of science, the physics of cosmic dust. The review by Voshchinnikov (2012) shows that the observed extinction, reddening, and R V vary extremely widely for different directions, distances, and wavelengths and sources of radiation. In recent years these have been described fairly well by theoretical models with different distribution of dust grains with respect to size, chemical composition, shape, and other properties.…”
Section: Changes In the Concept Of Interstellar Extinctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various models of diffuse dust have been developed to reproduce the polarization and extinction spectral dependences with a combination of aligned and unaligned grains (e.g., Lee & Draine 1985;Li & Greenberg 1997;Voshchinnikov 2012). The most recent are further constrained by fitting the (pre-Planck) spectral energy distribution of dust emission in the infrared and submillimetre (Draine & Fraisse 2009;Siebenmorgen et al 2014).…”
Section: Introductionmentioning
confidence: 99%